Nursing cooperation in implant-supported immediate restoration of edentulous jaws under dynamic navigation (基于以即刻修复为目标的动态导航下无牙颌种植手术护理配合) - MA Yu (马玉); YU Donghui (于冬辉); ZONG Jianting (宗建婷); CHEN Hongmei (陈红梅); SUN Feng (孙凤); MA Feifei (马斐斐) (中西医结合护理)
Objective To discuss the nursing strategy of dynamic navigation technology in the treatment of edentulous implantation with immediate restoration. Methods Totally 42 patients with edentulous jaws treated in First Clinical Division, Peking University School and Hospital of Stomatology from January 2019 to May 2023 were analyzed retrospectively. All the patients were treated with implant-supported immediate restoration of edentulous jaws under dynamic navigation. Nursing care experience was analyzed. Results Through preoperative design and dynamic navigation-assisted surgery, all the patients achieved successful immediate restoration with accurate location of implants and no complication. All the implant were placed at the correct position and achieved good initial stability. Immediate fixation and repair were completed, with a complication rate of 1. 59% at 6 months after surgery. Conclusion Dynamic navigation-assisted edentulous implantation requires nursing staff to get a good knowledge of related theories, appliance installment and software operation. Effective nursing plays important role in the treatment of dynamic navigation-assisted edentulous implantation. (回顾性分析基于以即刻修复为目标的动态导航下无牙颌种植手术的护理配合要点。方法 收集2019年1月—2023年5月收治的在动态导航系统引导下完成无牙颌种植手术伴即刻固定修复的42例患者的临床资料, 分析动态导航技术的应用情况及护理配合特点。结果 42例患者经过术前设计、术中导航均实现精确的种植体植入, 种植体就位率达100%, 并获得良好的初期稳定性, 完成即刻固定修复, 术后6个月并发症发生率为1. 59%。结论 动态导航辅助下的无牙颌种植手术需要护理人员熟练掌握动态导航理论知识、导航器械的安装使用及软件操作等相关技能, 做好充足的术前准备以及默契的术中护理配合, 以确保手术顺利完成。)